Hubungan Minat Belajar Dan Kemampuan Komunikasi Matematis Siswa Kelas VIII SMP - veronika veronika; Agung Prasetyo Abadi (Prosiding Sesiomadika, 2023)
The background of this research is the decreasing interest in learning and communication skills of students in mathematics. This study aims to determine whether there is a relationship between learning interest and students' mathematical communication skills in achieving learning success in the classroom. The method used is the quantitative method. In the observation session, students were given non-tests and tests, at the end of the lesson they were asked for their opinions about the tests they had done, unexpectedly the results were not good. The population in this study were students of SMPN 1 Cilebar, while the sample was class VIII D randomly selected as many as 26 students. The data collection in this study was in the form of a test of 3 description questions, then the score data was calculated using the average. Based on the results of the study, there was student recognition that they found it difficult when doing the existing tests and felt that the teacher who explained the material was too fast in explaining the explanation and how to fill it in, but they did not speak or ask directly when they did not understand what was explained.